Back on blossom street ebook - Macomber, Debbie (Blossom Street, 2008)
Blossom Street. Where you'll find everything you're looking for! From yarn and flowers to friendship... There's a new shop on Seattle's Blossom Street—a flower store called Susannah's Garden, right next door to A Good Yarn. Susannah Nelson, the owner, has just hired an assistant named Colette Blake, a young widow who's obviously hiding a secret—or two! When Susannah and Colette both join Lydia Goetz's new knitting class, they discover that Lydia and her sister, Margaret, have worries of their own. Margaret's daughter, Julia, is the victim of a random carjacking, and the entire family is thrown into emotional chaos. Then there's Alix Townsend, whose wedding is only months away. She's not sure she can go through with it, though. A reception at the country club, with hundreds of guests she's never met—it's just not Alix. But, like everyone in Lydia's knitting class, she knows there's a solution to every problem...and another woman can usually help you find it!